Palaeomagnetic study of the Eastern Kamchatka Cretaceous--Palaeocene island arc: new evidence concerning palaeosubduction zone absolute motion - Pechersky, D. M.; Shapiro, M. N.; Sharonova, Z. V. (Geophysical Journal International, 1997)
An important geodynamical problem is testing for the possibility of absolute displacement of subduction zones. To consider the above problem, the most favourable geological situations are those where (1) arc-related continuous volcanism existed long enough to store significant palaeolatitude changes occurring during the accumulation of volcanic sequences and (2) a significant meridional component of the studied block displacement occurred during volcanic activity. The Upper Cretaceous and Lower Palaeocene volcanic island-arc complexes of Eastern Kamchatka, which formed on the Pacific ocean during rapid northward drift, satisfy the above conditions. Palaeomagnetic and petromagnetic investigations of the Upper Cretaceous-Lower Palaeocene volcanics of the Kumroch Ridge at 12 localities (183 hand samples) were carried out to determine the movements of the subduction zone during volcanic activity. The major magnetic mineral in all rocks is low-Ti titanomagnetite, which is typical for island-arc basalt. Most of the titanomagnetite grains from basalts are homogenous, and their Curie points are 450°–500°C; a small fraction of the magnetic grains have T c =560°–580°C. Most of the titanomagnetite grains in tuffs have been oxidized to magnetite. NRM stepwise thermal demagnetization was carried out, together with principal component analysis. As a result of fold, baked contact, conglomerate and ‘long particles’ tests, the high temperature, close to the primary, ChRM component was found. Mean palaeomagnetic directions for four stratigraphic intervals from the base to the top of the sequence are: (1) D =32°, I =49°, α 95 =3.8°; (2) D =218°, I = −56°, α 95 =5.6°; (3) D =251°, I = −66°, α 95 =2.7°; (4) D =230°, I = −69°, α 95 =7.8°. The mean palaeolatitude changed from 30° to 53° during formation of the volcanic sequence. The drifting rate was 15–20 cm yr−1, which is close to the independent estimation of the Kula plate rate for the same time. According to palaeodeclinations, the area investigated was rotated clockwise 30°–70° ...